2017
DOI: 10.1007/s40596-017-0687-3
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study of a Spirituality Curriculum for General Psychiatry Residents

Abstract: Regardless of cultural or religious background, the residents endorsed the curriculum as a worthwhile experience and increased their appreciation of the place of spirituality in the holistic care of patients with psychiatric conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…Further details of this systematic review can be found elsewhere. 10 The eleven selected studies [13][14][15][16][17][18][19][20][21][22][23] were evaluated according to the following seven categories: residency year in which the intervention was implemented, course coordinator/faculty teaching methods, topics covered, evaluation tools and results (for the curriculum, residents, and patients), R/S competencies addressed, and recommended bibliography.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further details of this systematic review can be found elsewhere. 10 The eleven selected studies [13][14][15][16][17][18][19][20][21][22][23] were evaluated according to the following seven categories: residency year in which the intervention was implemented, course coordinator/faculty teaching methods, topics covered, evaluation tools and results (for the curriculum, residents, and patients), R/S competencies addressed, and recommended bibliography.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the articles presented a curriculum spread over several semesters of coursework [13][14][15][16]18,19,22,24 or were more concentrated initiatives 17,20,21,23 involving residents from different years. Some may defend the importance of the residents' prior clinical experience to better take advantage of the curriculum's content and discussion.…”
Section: When Should This Curriculum Be Taught?mentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited understanding regarding how medical residents perceive spirituality and religion's impact on medical care outside the specialty of psychiatry, which has reported trying to incorporate these topics into their training curricula. In previous studies of psychiatry resident knowledge, attitudes, and skills related to spirituality, religion, and medicine, most participants agreed spiritual and religious needs of patients are important to address in medical care, 5 and implementation of a spirituality and religion curriculum may lead to improvement in these measures. 6,7 The aim of our study was to perform a needs assessment of internal medicine resident knowledge, attitudes, and skill regarding spirituality, religion, and its intersection with medicine.…”
Section: Introductionmentioning
confidence: 99%
“… 4 In an effort to establish themselves as distinct scientific undertakings, it was necessary for disciplines such as psychiatry and behavioural sciences to distance themselves from religion. 5 Sigmund Freud, the founder of psychoanalysis described spiritual experiences as a ‘universal obsessional neurosis’, a form of ‘pathological thinking in need of modification’. 2 6 However, since the 1980s, there has been some literature to support the positive influences of SR on the physical and psychological well-being of individuals.…”
Section: Introductionmentioning
confidence: 99%